The effect of fasting to the quality of spermatozoa in adult male rattus norvegicus - Nur Azizah Hafaz (JKKI (Jurnal Kedokteran dan Kesehatan Indonesia), 2017)
Backround: Oxidative stress contributes in male infertility as a causative idiopathic factor. Fasting is one kind of physical stress that can also cause oxidative stress. Furthermore, oxidative stress would increase ROS concentration. The increase of ROS contributes to infertility and decrease of testis weight. A lot of studies had been conducted on more than 24 hours fasting which leads to reducing sperms quantity, volume, and motility. In the other hand, studies on fasting for less than 24 hours are still limited; therefore study to evaluate the effect of stress caused by fasting for less than 24 hours to the quality of spermatozoa in adult male mice is needed. Objective: To determine the effect of 10 hours and 12 hours fasting to the quality of spermatozoa which included its motility, viability, and morphology in adult male mice. Methods: This study is an experimental research. Three months old male Wistar mice were divided into 3 groups, in which each group contained 10 mice. Group 1 was the control group, group 2 was treated with 10 hours fasting for 14 days, and group 3 was treated with 12 hours fasting for 14 days. After the intervention, their sperm motility, viability, and morphology were observed. Motility and morphology data were analyzed using One-Way ANOVA test, whereas the viability data was analyzed using Kruskal. Results: The sperm’s motility, viability, and morphology of the control group were different from the two intervention groups (p < 0,05). Control group had significant difference compared to the group of 10 hours fasting and group of 12 hours fasting (p < 0,05). There was no significant difference between treatment groups (p > 0,05). Conclusion: 10 hours and 12 hours fasting affect the quality of sperm in adult male mice.